Antioxidant Activity of Chitosan Fishery Products combine gambir with glucose as a functional natural preservative for processed food - Selly Ratna Sari; Susiana Susiana; Guttifera Guttifera; Raudhatus Sa’daah (Universitas Sriwijaya, 2022)
The purposed study was to re-optimize preservation before it becomes a preservative solution, so this study was carried out to find the right formulation between glucose and gambir concentrations. The experimental design used was a complete Randomized Rancagan conducted with three groups. The treatment was gambir concentration (A): A1 = 2% A2 = 4% and A3 = 6%, using the same concentration of chitosan and glucose 1%. The research carried out during the proposal included sample preparation and modification between glucose chitosan and gambir into a preservative solution. Antioxidant testing is testing using the DPPH method The best antioxidant in the A1 treatment with the lowest IC50 value of 75.91% and the highest brown color in the A3 treatment, namely the treatment with a gambir concentration of 6%.